On multiple convolutions and time scales - Eltayeb, Hassan; Kilicman, Adem; Fisher, Brian (Hindawi Publishing Corporation, 2013)
The properties of the multiple Laplace transform and convolutions on a time scale are studied. Further, some related results are also obtained by utilizing the double Laplace transform. We also provide an example in order to illustrate the main result.